Magnetoresistance and transistor-like behavior of a double quantum-dot via crossed Andreev reflections - Siqueira, E. C. [UNESP]; Cabrera, G. G. (American Institute of Physics (AIP), 2012)
The electric current and the magnetoresistance effect are studied in a double quantum-dot system, where one of the dots QD(a) is coupled to two ferromagnetic electrodes (F-1; F-2), while the second QD(b) is connected to a superconductor S. For energy scales within the superconductor gap, electric conduction is allowed by Andreev reflection processes. Due to the presence of two ferromagnetic leads, non-local crossed Andreev reflections are possible. We found that the magnetoresistance sign can be changed by tuning the external potential applied to the ferromagnets. In addition, it is possible to control the current of the first ferromagnet (F-1) through the potential applied to the second one (F-2). We have also included intradot interaction and gate voltages at each quantum dot and analyzed their influence through a mean field approximation. The interaction reduces the current amplitudes with respect to the non-interacting case, but the switching effect still remains as a manifestation of quantum coherence, in scales of the order of the superconductor coherence length. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4723000]